Global pension crisis : unfunded liabilities and how we can fill the gap - Marin, Richard A., 1954- (Wiley finance series., 2013)
BA comprehensive look at the crisis of unfunded pension liabilities and what must be done to avoid the same problem in the future/b As the generational bubble of the Baby Boomers begins to retire, it is increasingly evident that governments, corporations, and individuals have failed to adequately prepare for the obligations and needs of this giant cohort. Retirees are outliving actuarial life expectancies, pension liabilities are skyrocketing, pension plans are underfunded, and medical costs rise, the United States alone can expect unfunded liabilities to exceed $4 trillion./ Even while the American economy shows signs of sustained recovery, states and local governments will still experience sharp increases in pension fund payments through the next year or longer. iGlobal Pension Crisis/i looks at this situation and offers practical advice for retirement plan managers and financial advisors, while also explaining how to strengthen pensions and prevent similar crises in the future./ ulliOffers a clear and comprehensive explanation of the current pension crisis for retirement fund managers, financial advisors, and economists/liliIncludes prescriptive guidance on how to strengthen the pension fund system and prevent another similar crisis/liliWritten by venture capitalist, entrepreneur, and former senior Wall Street executive Rich Marin/li/ul.